Understanding factors associated with continuation of intrauterine device use in Gujarat and Rajasthan, India: a cross-sectional household study. Issue 2 (10th January 2022) - Singal, Sunita; Sikdar, S. K.; Kaushik, S.; Singh, Pragati; Bhatt, Nidhi; Samandari, Ghazaleh; Pal, Manoj; Cagatay, Levent; Arya, Anupama; O'Connell, Kathryn A.
Abstract: The Government of India has promoted the expansion of access to and uptake of intrauterine devices (IUDs), during both the interval (IIUD) and postpartum (PPIUD) periods, as part of its Family Planning 2020 initiative. This study, conducted by EngenderHealth as part of the Expanding Access to IUD Services in India project, examines IIUD and PPIUD continuation rates over time and investigates factors associated with IUD continuation. We recruited respondents ( N  = 5024) through a repeated cross-sectional household study between February and December 2019. We identified respondents using IUD client data from public health facility registers in 20 districts of Gujarat and Rajasthan. We compared continuation rates for IIUD and PPIUD adopters and used regression analyses to measure the association between continuation and demographic, quality of care, and counselling variables. IIUD continuation rates decreased from 85.6% to 78.3% and PPIUD rates decreased from 78.5% to 70.7% between month 3 and month 12. Clients experiencing side effects or other problems were 15 times more likely to discontinue IUD use than clients who did not. Clients who received IUD counselling prior to insertion were more likely to continue than those who did not. IUD continuation increased significantly in cases where both partners jointly selected the method compared to situations where women decided alone. Several sociodemographic factors were associated with continuation. Our study demonstrates the value and benefits of programmes offering IUD services emphasising quality counselling and client-centred care to increase access, uptake, and continuation.